Computational studies for pre-evaluation of pharmacological profile of gut microbiota-produced gliclazide metabolites - Đanić, Maja; Pavlović, Nebojša; Zaklan, Dragana; Stanimirov, Bojan; Lazarević, Slavica; Al-Salami, Hani; Mikov, Momir (Frontiers in Pharmacology, 2024)
Background: Gliclazide, a second-generation sulfonylurea derivative still widely used as a second-line treatment for type 2 diabetes mellitus, is well known to be subject to interindividual differences in bioavailability, leading to variations in therapeutic responses among patients. Distinct gut microbiota profiles among individuals are one of the most crucial yet commonly overlooked factors contributing to the variable bioavailability of numerous drugs. In light of the shift towards a more patient-centered approach in diabetes treatment, this study aimed to conduct a pharmacoinformatic analysis of gliclazide metabolites produced by gut microbiota and assess their docking potential with the SUR1 receptor to identify compounds with improved pharmacological profiles compared to the parent drug.Methods: Ten potential gliclazide metabolites produced by the gut microbiota were screened for their pharmacological properties. Molecular docking analysis regarding SUR1 receptor was performed using Molegro Virtual Docker software. Drug-likeness properties were evaluated using DruLiTo software. Subsequently, the physicochemical and pharmacokinetic properties of gliclazide and its metabolites were determined by using VolSurf+ software package.Results: All studied metabolites exhibited better intrinsic solubility than gliclazide, which is of interest, considering that solubility is a limiting factor for its bioavailability. Based on the values of investigated molecular descriptors, hydroxylated metabolites M1-M6 showed the most pronounced polar and hydrophilic properties, which could significantly contribute to their in vivo solubility. Additionally, docking analysis revealed that four hydroxyl-metabolites (M1, M3, M4 and M5), although having a slightly poorer permeability through the Caco-2 cells compared to gliclazide, showed the highest binding affinity to the SUR1 receptor and exhibited the most suitable pharmacological properties.In silico study revealed that hydroxylated gut microbiota-produced gliclazide metabolites should be further investigated as potential drug candidates with improved characteristics compared to parent drug. Moreover, their part in the therapeutic effects of gliclazide should be additionally studied in vivo, in order to elucidate the role of gut microbiota in gliclazide pharmacology, namely from the perspective of personalized medicine.